Al Tadākhul Al Lughowi wa Ãtsarah ‘Ala Alta’bir Al Syafawi - Nurul Syahidah; Fahmi Ridha; Mada Wijaya Kusumah (Mauriduna: Journal of Islamic Studies, 2020)
قام الباحث بدراسة هذ الموضوع لمعرفة التدخل التركيبي الذي يقع لدى الطالبات ومعرفة تأثيره في التعبير الشفهي وتحليله. أما نوع هذا البحث هو البحث الوصفي التحليلي. جمعت البيانات عن طريق المراقبة والملاحظة والاطلاع إلى سجلات الأخطاء اللغوية من قبل قسم اللغة للجمعية الطلابية للبنات. أما تحليل البيانات المستخدم مبني على رأي ميلس وهبرمان. فحصل الباحث على النتائج: وقوع التدخل التركيبي لدى الطالبات وله أثر سلبي مؤثر في التعبير الشفهي وهو وقوع الأخطاء التركيبية في التعبير الشفهي باللغة العربية. وذلك لأسباب التالية وهي الاعتقاد الخاطئ، والتسهل، والغفلة عن التراكيب النحوية، نقل تراكيب اللغة الأم، والاعتماد على الترجمة الإندونيسية، التراكيب صحيحة في رأيه. The researcher studied this topic to find out the structural disruptions that spread among the students and their impact on ta’bīr syafahī and its analysis. This research used analytical descriptive research. Data were collected by observation, and access to linguistic error recorded by Linguistic Society. The analysis of user data is based on Miles and Huberman's opinion. The researcher has obtained some results: The occurrence of structural interventions among students and a negative impact on ta’bīr syafahī, which is the occurrence of syntactic errors in ta’bīr syafahī in Arabic. This is caused by some reasons i.e misunderstanding, simplification, negligence of grammatical structures, transmission of mother tongue structures, dependency on Indonesian translation, over self confidence in making sentences.